THE LEGALITY OF HUMAN RIGHTS LIMITATIONS IMPOSED BY COVID-19 GREEN PASSES IN LITHUANIA AND THE CZECH REPUBLIC - Violeta Vasiliauskienė; Birutė Pranevičienė; Lenka Scheu; Filip Dostál (International Comparative Jurisprudence, 2023)
The aim of this article is to provide a comparative analysis of the regulation of the Opportunity Passport (hereinafter OP – aCOVID-19 health status certificate) in Lithuania and an analogous document in the Czech Republic, and the legality of the limitations onhuman rights that were imposed by such rules. It describes the regulations imposed by the Lithuanian and Czech institutions and theirdevelopment. Further, the requirement of the legality of limitations on human rights is discussed in the context of its application to the OPregulation, taking into consideration the jurisprudence of the Constitutional Court of Lithuania. The article also analyses the Tečkaapplication, which was used for analogous purposes in the Czech Republic, in terms of its legal basis and problems related to the legalityof human rights violations. The critical analytical method allows for an analysis of Lithuanian and Czech legislation on the managementof the pandemic, the establishment of so-called green passports, and the relevant jurisprudence of the courts, leading to well-groundedconclusions. This method is also employed in the analysis of scientific literature, which allows concerns to be revealed regarding dataprotection in the process of the execution of the above-mentioned provisions. The comparative method allows the authors to compare thepractice of the selected two states in the management of the pandemic and in the adoption of green passports. The article concludes thatboth documents regarding health status during the COVID-19 pandemic had similar aims and were introduced at similar times. However,the legal regulation of the Lithuanian OP has not yet been analysed by the courts. In Lithuania, the legality of the OP was questioned basedon the fact that the relevant law on the protection of public health contains only succinct provisions on the limitation of human rights insuch situations, and the question remains as to whether these provisions were sufficient for such limitations. In the Czech Republic, theconcern was raised about the authority of the Ministry of Health to issue such documents as it had no legal basis. Furthermore, questionsof privacy in the context of the Czech health passport were also pertinent.